2021
DOI: 10.31083/j.rcm2202048
|View full text |Cite
|
Sign up to set email alerts
|

Costs associated with transradial access and same-day discharge after percutaneous coronary intervention: a systematic review and meta-analysis

Abstract: Transradial access for PCI (TRI) along with same day discharge (SDD) is associated with varying estimates of cost savings depending on the population studied, the clinical scenario and application to low-risk vs high-risk patients. A summary estimate of the true cost savings of TRI and SDD are unknown. We searched the PubMed, EMBASE®, CINAHL® and Google Scholar® databases for published studies on hospitalization costs of TRI and SDD. Primary outcome of interest in all included studies was the cost saving with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…The financial impact of using this protocol in Brazil remains unknown, but international experiences suggest cost reductions. [1][2][3][4] The most recent meta-analysis on costeffectiveness estimates savings of US$ 3,567.58 (95%CI US$ 2,303.39-US$ 4,831.78) per PCI performed in an SDD setting. In the subgroup analysis, it was identified that the cost of hospitalization is the only one that has a statistically significant impact on cost savings.…”
Section: Financial Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…The financial impact of using this protocol in Brazil remains unknown, but international experiences suggest cost reductions. [1][2][3][4] The most recent meta-analysis on costeffectiveness estimates savings of US$ 3,567.58 (95%CI US$ 2,303.39-US$ 4,831.78) per PCI performed in an SDD setting. In the subgroup analysis, it was identified that the cost of hospitalization is the only one that has a statistically significant impact on cost savings.…”
Section: Financial Impactmentioning
confidence: 99%
“…The transradial access approach plays a fundamental role in this aspect, as it has been shown to correlate with lower cost and faster discharge, including same-day discharge (SDD). [1][2][3][4] Much of the benefit of the access route is due to the safety of the route and its lower rate of complications, which could extend the patient's hospital stay. 5,6 Different series globally have evaluated SDD after elective PCI.…”
Section: Introductionmentioning
confidence: 99%